Eclips : 25 jaar = 25th anniversary Deweer Art Gallery. - Deweer, Mark, ....-; Van de Velde, Filip, ....- (Zwevegem-Otegem : Deweer Art Gallery Zwevegem - Otegem, 2004)
Balkenhol, Stephan ; Baselitz, Georg ; Bratkov, Sergey ; Brus, Johannes ; Carroll, Lawrence ; De Cock, Jan ; Cragg, Tony (Anthony) ; Cucchi, Enzo ; Fabre, Jan ; Förg, Gunther ; Höckelmann, Antonius ; Kabakov, Ilya ; Knoebel, Imi ; Lafontaine, Marie-Jo ; Lange, Thomas ; Laurette, Matthieu ; Merz, Gerhard ; Mik, Aernout ; Müller, Josef Felix ; Paladino, Mimmo ; Panamarenko ; Solakov, Nedko ; Tahon, Johan ; Vandekerckhove, Hans ; Vanmechelen, Koen
Engels
Nederlands
Keywords: Catalogs; Exhibition catalogs